Production and counting of spores of Clostridium chauvoei. - Bagadi, H O (1977)
The concentration and viability of spores produced by four different strains of Clostridium chauvoei (C. feseri) grown in a modified medium for 18 days are described. The medium yielded enough viable spores for experimental work.